2016
DOI: 10.1002/smll.201602272
|View full text |Cite
|
Sign up to set email alerts
|

Alignment under Magnetic Field of Mixed Fe2O3/SiO2Colloidal Mesoporous Particles Induced by Shape Anisotropy

Abstract: When using the bottom-up approach with anisotropic building-blocks, an important goal is to find simple methods to elaborate nanocomposite materials with a truly macroscopic anisotropy. Here, micrometer size colloidal mesoporous particles with a highly anisotropic rod-like shape (aspect ratio ≈ 10) have been fabricated from silica (SiO ) and iron oxide (Fe O ). When dispersed in a solvent, these particles can be easily oriented using a magnetic field (≈200 mT). A macroscopic orientation of the particles is ach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 32 publications
(39 reference statements)
3
15
0
Order By: Relevance
“…In a previous study, we already designed promising γ‐Fe 2 O 3 and ϵ‐Fe 2 O 3 /mesoporous silica particles with a long rod morphology, and we have shown that they undergo macroscopic alignment when submitted to an external magnetic field . Here, we extend this study to the preparation of ϵ‐Fe 2 O 3 /mesoporous silica nanocomposites with two other shapes for the mesoporous silica hard template, namely platelet and donut.…”
Section: Introductionmentioning
confidence: 75%
See 3 more Smart Citations
“…In a previous study, we already designed promising γ‐Fe 2 O 3 and ϵ‐Fe 2 O 3 /mesoporous silica particles with a long rod morphology, and we have shown that they undergo macroscopic alignment when submitted to an external magnetic field . Here, we extend this study to the preparation of ϵ‐Fe 2 O 3 /mesoporous silica nanocomposites with two other shapes for the mesoporous silica hard template, namely platelet and donut.…”
Section: Introductionmentioning
confidence: 75%
“…For fabrication of ϵ‐Fe 2 O 3 nanocrystals inside the mesochannels by solvent‐free impregnation, the same procedure was followed for the three samples, with a thermal treatment under air at 1000 °C, as detailed in the experimental section and in Table . Figure shows the evolution of the SAXS patterns for the three kinds of samples after one and two impregnations.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In that case the ZFC maximum is close to the value expected for diluted nanocrystals. Magnetic shape anisotropy arising from dipolar interaction within single-chains of nanoparticles was already evidenced in ordered mesoporous silica powders containingc hains of metallic Co nanoparticles [23] or iron oxide particles [24] and in iron oxide nanoparticles assembled in chains that were prepared ChemNanoMat 2017, 3,833 -840 www.chemnanomat.org by soft templating based on bacteria [25] and organic molecules, [26] or inducedb yamagnetic field. [27] To the besto fo ur knowledge,t his is the first example of enhanced collective properties induced by the directed assembly of coordination nanocrystals into 1D-chains.…”
Section: Discussionmentioning
confidence: 99%